Thromboprophylaxis in the Sars-Cov-2 hospitalized patient - Cotrina-Pereyra, Rosa (2021)
Introduction: Patients with the SARS-CoV2 virus are hospitalized for pneumonia and acute respiratory failure. Hypercoagulability, micro and macro thrombosis appear in them. The severe increase in D-dimer has led to the use of thromboprophylaxis with doses higher than the standard with controversial results. The present article aims to guide the physician in a rational thromboprophylaxis to reduce thrombotic complications and avoid bleeding associated with anticoagulation and underlying disease. The results of randomized controlled clinical trials for optimal management of the hypercoagulable state are awaited.